2021
DOI: 10.1186/s40478-021-01120-x
|View full text |Cite
|
Sign up to set email alerts
|

Prion-induced photoreceptor degeneration begins with misfolded prion protein accumulation in cones at two distinct sites: cilia and ribbon synapses

Abstract: Accumulation of misfolded host proteins is central to neuropathogenesis of numerous human brain diseases including prion and prion-like diseases. Neurons of retina are also affected by these diseases. Previously, our group and others found that prion-induced retinal damage to photoreceptor cells in mice and humans resembled pathology of human retinitis pigmentosa caused by mutations in retinal proteins. Here, using confocal, epifluorescent and electron microscopy we followed deposition of disease-associated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
2
6
0
1
Order By: Relevance
“…The results described above warrant further investigation on the accumulation of aggregated protein in the photoreceptors, especially since it appears as one of the events leading to photoreceptor death, as suggested by our RNA-Seq analyses and also by another group (51).…”
Section: Altered Gene Expression In Rods Of Adipor1 -/Mice and Its Association With Neurodegenerative Diseasessupporting
confidence: 61%
“…The results described above warrant further investigation on the accumulation of aggregated protein in the photoreceptors, especially since it appears as one of the events leading to photoreceptor death, as suggested by our RNA-Seq analyses and also by another group (51).…”
Section: Altered Gene Expression In Rods Of Adipor1 -/Mice and Its Association With Neurodegenerative Diseasessupporting
confidence: 61%
“…Our findings confirm prior reports of retinal PrP Sc deposition in sCJD cases ( Head et al, 2003 , 2005 ; Orru et al, 2018 ; Takao et al, 2018 ) as well as in mouse models ( Striebel et al, 2021 ). As with these studies, we find the strongest PrP Sc deposition in the OPL where discrete ovoid deposits of PrP Sc result in a “beads-on-a-string” appearance along the horizontal length of the lamina.…”
Section: Introductionsupporting
confidence: 93%
“…Although further ultrastructural investigations of the structures involved in the OPL PrP Sc deposits are warranted, we hypothesize that PrP Sc is accumulating at the synaptic ribbon where the presynaptic terminals of rod and cone photoreceptors from the ONL connect with the postsynaptic dendrites of bipolar and amacrine interneurons from the INL. Evidence of this PrP localization has recently been reported by Striebel et al (2021) , who identified PrP Sc accumulation in ribbon synapses and cilia of photoreceptors in mouse models of prion disease. The presence of PrP Sc deposits at retinal synaptic junctions could alter or disrupt this retinal circuitry, result in photoreceptor degeneration, and perhaps contribute to visual symptoms reported in sCJD.…”
Section: Introductionmentioning
confidence: 65%
“…In addition, a previous study has reported that prion-induced photoreceptor degeneration begins with PrP Sc accumulation in cones at two distinct sites including cilia and ribbon synapses. This result indicated the association of cilium-related biological processes with prion disease in the retina [ 31 ]. Although there was no validation at the RNA level for the differentially expressed genes found in this study, since several pieces of evidence have indicated the association of cilium with prion diseases, further investigation of cilium in prion diseases at the protein level is highly desirable in the future.…”
Section: Discussionmentioning
confidence: 99%